Morocco : 2006 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Morocco. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The macroeconomic environment is sound, with low inflation and a comfortable external position, although the fiscal position remains a concern for the medium term. The authorities have successfully privatized and liberalized the telecommunications, energy, and transportation sectors. Moreover, Morocco has significantly liberalized its trade regime and strengthened its financial sector. These reforms have enhanced the overall productivity of the economy and heightened its resilience to shocks. The medium-term outlook is favorable. The government debt-to-GDP ratio has declined steadily since the turn of the century.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet